Optimization of Extraction and Dyeing Parameters for Natural Dyeing of Cotton Fabric Using Marigold (Tagetes erecta) - Farooq, Assad; Ali, Shaukat; Abbas, Naheed; Zahoor, Naila; Azeem Ashraf, Muhammad (Asian Journal of Chemistry, 2013)
The present work involves the optimization of extraction and dyeing recipes to standardize the procedure for natural dye obtained from the petals of marigold (Tagetes erecta). The resultant dye obtained at optimized extraction conditions was applied on cotton fabric to study the effect of temperature, time, material to liquid ratio (M:L), salt concentration and mordanting. Colorimetric data and colour fastnesses were studied for evaluation of optimum extraction and dyeing conditions. It was observed that extraction and dyeing parameters have significant effect on colour characteristics of dyed cotton fabric. The optimized extraction conditions were; M:L ratio 1:20, extraction time 90 min and temperature 100 ºC while optimized dyeing parameters were; M:L ratio 1:30, dyeing time 1 h and temperature 90 ºC and salt concentration 60 g/L of sodium sulphate. Better light and washing fastness were obtained in case of post mordanting with ferrous sulphate.